APPLYING MODERN PORTFOLIO THEORY TO PLANT ELECTRICITY PLANNING IN ALBANIA - Tola, Matilda (European Scientific Journal, ESJ, 2015)
Resource planning has achieved a great deal of attention from researches these last decades; and energy resource planning has its share of importance. Since the problem of Global Warming, became imminent, researches of all kind are striving to find new, more environment friendly solutions to meet their energy demands. Due to technology limitations, and systemic risks, renewable resources still are exploited poorly and most of the generation depends on fossils. A growing body of literature proves that shortage of energy supply affects directly economic growth, so we face this challenge: “How to produce cleaner energy with maximum reliability?” Albania generates electricity 100% from hydro resources. Even though there have been a lot of new investments in power generating sector, we believe that we are still exposed to an excessive amount of risk because of lack of diversification. So, this paper addresses issues on planning electric generation supply to achieve maximum reliability for Albania, by analyzing present generation risk from hydro resources and considering diversification effect on Albania’s electricity generating portfolio. We begin by analyzing to day work that support portfolio planning in power sector. Then we address the Modern Portfolio Theory and analyze how it proposes solutions to an optimization problem. After that we take a brief overview of the power sector current situation and its dependence on import. By using a small simulation we will try to demonstrate that adding new generating technologies can reduce risk and improve power generation.